Toward a Biological, Psychological and Familial Approach of Eating Disorders at Onset: Case-Control ANOBAS Study - Sepúlveda, Ana Rosa; Moreno-Encinas, Alba; Martínez-Huertas, José Angel; Anastasiadou, Dimitra; Nova, Esther; Marcos, Ascensión; Gómez-Martínez, Sonia; Villa-Asensi, José Ramón; Mollejo, Encarna; Graell, Montserrat (Frontiers in Psychology, 2021)
Eating disorders (ED) are considered as heterogeneous disorders with a complex multifactor aetiology that involves biological and environmental interaction. Objective: The aim was to identify specific ED bio-psychological-familial correlates at illness onset. Methods: A case-control (1:1) design was applied and we studied 50 adolescents diagnosed with ED at onset (12-17 years old) and their families, paired by age and parents’ socio-educational level with 3 control samples, 40 with an affective disorder, 40 with asthma and 50 with no pathology, and their respective families. Biological, psychological and familial correlates were assessed using interviews, standardised questionnaires and blood test. Results: After performing conditional logistic regression models for each type of variable, those correlates that showed to be specific for ED were included in a global exploratory model (R2 = .44). The specific correlates identified associated to the onset of an ED are triiodothyronine (T3) as the main specific biological correlate; patients’ drive for thinness, perfectionism and anxiety as the main psychological correlates; and fathers’ emotional over-involvement and depression and mothers’ anxiety as the main familial correlates. Conclusions: To our knowledge, this is the first study to use three specific control groups assessed through standardized interviews, and to collect a wide variety of data at illness onset. This design exploring which correlates, among those measured, are specific to the EDs, showing that perfectionism and family emotional over-involvement, as well as the T3 hormone are relevant to discern ED cases at onset from other adolescents with or without pathology.